Female Foeticide in Delhi/NCR: Exploring the Socio-Economic and Cultural Dimensions - Deb , Roumi; Bhatnagar P; Avasthy D (National Journal of Community Medicine, 2012)
Background: The social and psychological fibres of India are predominantly patriarchal and contributing extensively to the secondary status of women. It is yet to be seen if the difference in attitudes towards the practice of female foeticide varies in different socio-economic strata, and in among the different communities of India. Methodology: The present study is based on a door-to-door survey comprising 100 families, conducted in slum areas of Delhi/NCR. Most of the families living in these areas were immigrants from different states of India with different cultural practices and beliefs. Results: Though the studied participants differed in their cultural perceptions on role and status of women in society, majority of them testified that the practice is more prevalent in the middle and upper class society, and escalating demands of dowry was cited as the main reason behind it. Conclusion: The extent of practice of female foeticide is seen to vary among different socio-economic strata and communities. Taking this diversity into consideration, customized social-awareness campaigns must be organized in accordance with different cultural and socioeconomic circumstances existing in the diverse range of communities in India.